The Proximal Airway Is a Reservoir for Adaptive Immunologic Memory in Idiopathic Subglottic Stenosis. (30th June 2020) - Gelbard, Alexander; Wanjalla, Celestine; Wootten, Christopher T.; Drake, Wonder P.; Lowery, Anne S.; Wheeler, David A.; Cardenas, Maria F.; Sikora, Andrew G.; Pathak, Ravi R.; McDonnell, Wyatt; Mallal, Simon; Pilkinton, Mark
Abstract : Objectives/Hypothesis: Characterization of the localized adaptive immune response in the airway scar of patients with idiopathic subglottic stenosis (iSGS). Study Design: Basic Science. Methods: Utilizing 36 patients with subglottic stenosis (25 idiopathic subglottic stenosis [iSGS], 10 iatrogenic post‐intubation stenosis [iLTS], and one granulomatosis with polyangiitis [GPA]) we applied immunohistochemical and immunologic techniques coupled with RNA sequencing. Results: iSGS, iLTS, and GPA demonstrate a significant immune infiltrate in the subglottic scar consisting of adaptive cell subsets (T cells along with dendritic cells). Interrogation of T cell subtypes showed significantly more CD69 + CD103 + CD8 + tissue resident memory T cells (TRM ) in the iSGS airway scar than iLTS specimens (iSGS vs. iLTS; 50% vs. 28%, P = .0065). Additionally, subglottic CD8 + clones possessed T‐cell receptor (TCR) sequences with known antigen specificity for viral and intracellular pathogens. Conclusions: The human subglottis is significantly enriched for CD8 + tissue resident memory T cells in iSGS, which possess TCR sequences proven to recognize viral and intracellular pathogens. These results inform our understanding of iSGS, provide a direction for future discovery, and demonstrate immunologic function in the human proximal airway. Laryngoscope, 131:610–617, 2021